2002
DOI: 10.1002/ajhb.10081
|View full text |Cite
|
Sign up to set email alerts
|

Secular trend in the development of fatness during childhood and adolescence

Abstract: This study examined the development of fatness, as indexed by skinfold thickness, in healthy Caucasian children and adolescents residing in the same location in Canada in the 1960s and the 1990s. The data comes from two longitudinal studies, conducted approximately 30 years apart, of children aged 8-16 years. The first study (1964-1973) annually measured 207 males and 140 females. The second investigation (1991-1997) repeatedly measured 113 males and 115 females. Identical measurement tools and protocols were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
(28 reference statements)
5
29
0
2
Order By: Relevance
“…Humans have been described as a primate species evolving to accumulate fat (Pond 1996;Kuzawa 1998). The higher average percentage fat mass in humans, however, may be the result of the modern lifestyle, as a recent study has shown that the fatness of children and adolescents increased from the 1960s to the 1990s (Thompson et al 2002).…”
Section: Obesity and Leanness In Japanese Macaquesmentioning
confidence: 97%
“…Humans have been described as a primate species evolving to accumulate fat (Pond 1996;Kuzawa 1998). The higher average percentage fat mass in humans, however, may be the result of the modern lifestyle, as a recent study has shown that the fatness of children and adolescents increased from the 1960s to the 1990s (Thompson et al 2002).…”
Section: Obesity and Leanness In Japanese Macaquesmentioning
confidence: 97%
“…A study conducted in the USA with 7-17-year-old children and adolescents showed that the relationships between anthropometric measures (WC, waist-to-hip ratio, triceps, suprailiac and subscapular SFT, and SFT ratios) and body fat distribution (measured by dual-energy X-ray absorptiometry) all depended on age, and that some of the measures were also dependent on gender, race or body fat percentage (44) . Other biological variables that affect height and body composition must be investigated to determine the reasons for the secular trend towards increased adiposity among children and adolescents, such as age at sexual maturation (12) . Unfortunately, this information was not obtained in our sample of 7-10-year-old children and was not included for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measures of adiposity include skinfold thicknesses (SFT) and waist circumference (WC). SFT, a measure of subcutaneous adipose tissue, is well correlated with total body fat mass (10) and has been used to monitor adiposity in population studies (11,12) . WC and waist-to-height ratio (WHtR) are highly sensitive measures of central body fat accumulation that predict adverse cardiovascular risk factors (13,14) .…”
mentioning
confidence: 99%
“…The study has been described in detail elsewhere (Mirwald, 1978;Thompson, Baxter-Jones, Mirwald, & Bailey, 2002). In brief, in 1964 207 seven year old boys were randomly selected in to the study and were continuously assessed annually until 1973, when 16 years of age.…”
Section: Participantsmentioning
confidence: 99%